2010
DOI: 10.1093/europace/euq326
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-pulmonary vein foci with an EnSite array in patients with paroxysmal atrial fibrillation

Abstract: Non-PV foci are prevalent in the LA roof and SVC sites, but can originate from other sites as well. When non-PV foci are observed, PVI may be insufficient and should be supplemented with non-PV foci ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…24,25 We achieved success with a single PVI procedure in terms of freedom from AF and MRT for >80% of our patients, which is a high success rate among related studies to date. 20,26 Furthermore, in the groups with a large PVAI (groups III and IV), only 1 of 55 patients (1.8%) suffered from AF recurrence.…”
Section: Mechanism Of Af and Mrt Recurrences And Clinical Implicationmentioning
confidence: 58%
“…24,25 We achieved success with a single PVI procedure in terms of freedom from AF and MRT for >80% of our patients, which is a high success rate among related studies to date. 20,26 Furthermore, in the groups with a large PVAI (groups III and IV), only 1 of 55 patients (1.8%) suffered from AF recurrence.…”
Section: Mechanism Of Af and Mrt Recurrences And Clinical Implicationmentioning
confidence: 58%
“…Other possibilities include the presence of non-PV triggers and an ostial level of electric isolation that largely excludes areas in the antrum that may be responsible for the initiation and perpetuation of AF. 16,17 We previously have shown that the level of electric isolation with the first generation VGLA catheter is at the PV ostium. 2 The level of isolation with the current generation VGLA catheter has not been systematically evaluated.…”
Section: Efficacy Of the Vgla Cathetermentioning
confidence: 99%
“…All 75 patients had ectopies initiating AF or AT; 48 of these patients had PV foci alone (59 foci) and 17 had non-PV foci (19 foci). 33 It was noted that 71% of the patients with non-PV foci had PV foci as well. The non-PV foci were frequently located at the LA roof and SVC, with less frequent locations in the LA, RA, CS ostium and so on.…”
Section: Atrial Fibrillation (Af)mentioning
confidence: 99%
“…30 The PVs play an important role in initiating and maintaining AF in AF patients, and PV isolation is the cornerstone of all procedures of AF ablation, 31,32 in which AF is eliminated in 80-90% of those with paroxysmal AF and in 60-70% of those with persistent AF, depending on the ongoing AF duration. 28,29 Non-PV foci are also found in 20% of AF patients, 33 which is related to recurrence after PV isolation. Episodes from non-PV foci are unpredictable and transient, and can easily change into AF.…”
Section: Atrial Fibrillation (Af)mentioning
confidence: 99%